2011
DOI: 10.5551/jat.8094
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in the Japan Population: Association with Blood Lipid Levels and Effects in Reducing Cardiovascular and All-Cause Mortality

Abstract: According to many prospective cohort studies and meta-analyses of those studies, physical inactivity and/or low levels of physical fitness are associated with an elevated risk for the development of metabolic syndrome, type 2 diabetes, hypertension, coronary artery disease (CAD), and stroke, and with an increased risk of cardiovascular disease (CVD) mortality and all-cause mortality. Most of these analyses, however, were conducted on non-Japanese populations in the West. This report summarizes prospective obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 77 publications
0
39
1
Order By: Relevance
“…Daily physical activity has consistently been shown to reduce abdominal or overall obesity, and improve glucose homeostasis, insulin sensitivity, blood pressure and circulating lipoprotein profile, whether in developing ( 6 , 67 – 69 ) or developed ( 70 , 71 ) country populations. The central role of physical activity in CVD prevention ( 72 , 73 ) is widely recognised. Several African studies ( 68 , 69 , 74 ) have reported that rural populations have higher physical activity than their urban counterparts, with high-income groups in urban areas being less active than low-income ones.…”
Section: Discussionmentioning
confidence: 99%
“…Daily physical activity has consistently been shown to reduce abdominal or overall obesity, and improve glucose homeostasis, insulin sensitivity, blood pressure and circulating lipoprotein profile, whether in developing ( 6 , 67 – 69 ) or developed ( 70 , 71 ) country populations. The central role of physical activity in CVD prevention ( 72 , 73 ) is widely recognised. Several African studies ( 68 , 69 , 74 ) have reported that rural populations have higher physical activity than their urban counterparts, with high-income groups in urban areas being less active than low-income ones.…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic exercise is consistently associated with favorable shifts in blood triglycerides and HDL-C; however, data from intervention studies [1, 2] and numerous meta-analyses [36] also support a less well-characterized and variable LDL-C lowering response to exercise training. Beyond LDL-C lowering, lipoprotein-profiling studies also suggest that high-intensity exercise training may modulate LDL particle number and size distribution patterns [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…[75][76][77][78][79][80] However, no source could be identified that related directly to the population eligible for the intervention (those aged between 40 and 64 years inclusive), those who participated in the intervention (who tended to be drawn disproportionately from the older ages within the pool of those eligible) or the particular physical activity measures recorded by the Actiheart system. Column 2 is drawn from trial participants' ages.…”
Section: Discountingmentioning
confidence: 99%